EXPLORING CRYPTOCURRENCY ADOPTION TRENDS IN EUROPE: A COMPARATIVE ANALYSIS OF GERMANY, FRANCE, AND ROMANIA - Valentin Gabriel CRISTEA (Challenges of the Knowledge Society)
Cryptocurrencies have emerged as a significant innovation in the financial landscape, with their adoption varying across different regions. This paper investigates the adoption trends of cryptocurrencies in three European countries: Germany, France, and Romania. By examining regulatory frameworks, public sentiment, and market dynamics, we aim to provide insights into the factors influencing cryptocurrency adoption in these nations. Furthermore, we explore the relationship between digital banks and cryptocurrencies, analysing the potential synergies and challenges associated with their integration. Finally, we offer future projections and suggest areas for further research to better understand the evolving landscape of cryptocurrencies in Europe. The motivation for studying cryptocurrency adoption in Europe stems from the region's diverse regulatory frameworks, cultural attitudes, and economic landscapes. Understanding the dynamics of cryptocurrency adoption in specific European countries can provide valuable insights into the broader trends shaping the future of finance. Moreover, as digital banking continues to gain prominence, exploring the intersection between digital banks and cryptocurrencies becomes imperative. The regulatory frameworks surrounding cryptocurrencies in Germany, France, and Romania exemplify the diverse approaches adopted by European countries in response to the emergence of digital assets. While Germany and France have made significant strides in implementing comprehensive regulatory frameworks, Romania's regulatory landscape remains in the early stages of development.